Comparing the prevalence and influencing factors of postpartum depression in primiparous and multiparous women in China - Zhang, Jing; Wang, Peipei; Fan, Weisen; Lin, Cuixia (Frontiers in Psychiatry, 2024)
Background: Few studies have compared the influencing factors of postpartum depression between primiparous and multiparous women. Therefore, this study is aimed to investigate the prevalence and influencing factors of postpartum depression in primiparous and multiparous women, and provide reference suggestions for clinical nursing. Methods: A total of 429 postpartum women who gave birth at a Maternal and Child Health Hospital in Shandong Province, China, from April to June 2024, were recruited by convenience sampling. A Sociodemographic Questionnaire, Edinburgh Postpartum Depression Scale, Pittsburgh Sleep Quality Index, and Perceived Social Support Scale were used for investigation. SPSS 26.0 was used to analyze the data, and multivariate regression was employed to analyze the influencing factors of postpartum depression between primiparous and multiparous women. Results: The total prevalence of postpartum depression among 429 postpartum women (191 primiparas and 238 multiparas) was 22.14%. The prevalence of postpartum depression among primiparous and multiparous women were 21.99% and 22.27%, respectively, with no statistically significant difference [OR=1.016, 95% CI (0.642, 1.608)]. Sleep quality is a common protective factor for postpartum depression in both primiparous and multiparous women, while perceived social support is another protective factor for multiparous women. The risk factors are different in both two group, there is no risk factor found in primiparous women, the newborns health and women's expectation on newborns gender are risk factors for postpartum depression in multiparous women. Conclusions: Both primiparous and multiparous women have a high risk of postpartum depression. In order to promote the mental health of postpartum women, precise nursing measures should be adopted for different parity of postpartum women in clinical practice.